The fairy ring, or, Elsie and Frances fool the world - Losure, Mary. (Somerville, Mass. : Candlewick Press, 2012)
Relates the story of two early-twentieth-century cousins who believed they saw real fairies, created photographs using paper cutouts when they were teased by adult family members, and inadvertently drew the attention of Sir Arthur Conan Doyle, a fellow believer.
Keywords: Wright, Elsie, -- 1901-1988 -- Juvenile literature; Griffiths, Frances, -- 1907-1986 -- Juvenile literature; Fairies -- England -- Juvenile literature; Doyle, Arthur Conan, -- 1859-1930 -- Juvenile literature